Organizational Communication Culture at Elementary School - Budi Setiawan Ginting; Mesiono Mesiono; Uswatun Hasanah; Muhammad Irwansyah; Rija Ansyari (Jurnal Basicedu, 2023)
Learning and all educational activities in madrasas are strongly influenced by the organizational culture of communication adopted by the principal of the madrasa. This study aims to describe the culture of organizational communication at MI Kesuma LKMD Namorambe. To systematically parse the topic of this research, the researchers used a qualitative approach with a descriptive study method. The research informants totaled 5 teachers who worked at MI Kesuma LKMD Namorambe, then the data collection used in the application of this research included in-depth interviews, participant observation, focus group discussions, and document analysis. The results of this study concluded that the culture of organizational communication that implements MI Kesuma LKMD Namorambe in carrying out operational activities and implementing work, is practiced by teachers with the concept of having a relationship in the form of forming teacher communication during the process of carrying out work at MI Kesuma LKMD Namorambe. This is based on the indicators applied in this study. so that with this in mind, the researcher provides advice to MI Kesuma LKMD Namorambe regarding the organizational communication culture that is applied to schools which is classified as good (effective), so that it must always be maintained by school residents through providing a good example from the head of the madrasa to existing teachers, so that later teachers who work at MI Kesuma LKMD Namorambe also have a high level of loyalty.